A preliminary study on the use of transcutaneous electrical nerve stimulation to relieve post-operative pain in an attempt to improve respiratory function - Butow, Lucille (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc. (Physio)) - University of Stellenbosch, 1984.